Grouping оf Complexes оf Multiphase Queuing Systems - Zholtkevych, Г.Н.; Nazyrov, З.Ф.; Ignatov, С.Ю. (Journal of Information Technologies in Education (ITE), 2009)
Issues of classification of the complexes of multiphase queuing system systems in correspondence with entrance-output correlations and automatic grouping of complexes by the analysis of the graph of final product composition is examined in this work.